AW-NI-4: MAY MEASUREMENT MONTH 2021: AN ANALYSIS OF BLOOD PRESSURE SCREENING RESULTS FROM NEPAL. (January 2023) - Inagaki, Yoko; Koilala, Sweta; Poudel, Kiran; Tiwari, Kiran; Sapkota, Abhishek; Soti, Pabitra Babu; Neupane, Dinesh
Abstract : Objective: This study presents the result of May measurement Month 2021 in Nepal, a global initiative of the International Society of Hypertension (ISH) aiming to screen high blood pressure and raise awareness at the population level. Design and Methods: An opportunistic cross-sectional survey of> = 18 years of age was conducted in 15 out of 77 districts from September-December 2021. The trained enumerators administered the structured questionnaire of the ISH adopted into Nepali and took three blood pressure (BP) readings while in a sitting position at 1-minute intervals, using electronic BP machines. Participants were identified with hypertension using the following criteria: 1) mean of the 2nd and 3rd BP readings> = 140/90 mmHg or 2) being on at least one antihypertensive medicine taken for raised BP. Ethical approval was obtained from the Nepal Health Research Council. Results: A total of 5, 172 participants were included. The median age was 37.0 (IQR 25–51) years and 49.9 % were female. Self-reported tobacco use, alcohol drinking, diabetes, and history of myocardial infarction (MI) or stroke were reported in 21.7%, 21.9%, 4.1%, and 0.5% of participants, respectively. The mean of 2nd and 3rd BP readings or history of anti-hypertensive medication use were available for 5, 167 participants. The mean was 123.9 mmHg ± 10.3 for systolic blood pressure, and 81.2 mmHg ± 9.3 for diastolic blood pressure. 1, 066 (20.6%) met the criteria for hypertension, of which 399 (39.5%) were aware and 298 (29.5%) were treated with at least one anti-hypertensive medicine. Of those who were treated, 167 (56.0%) had their BP under control. With the BP threshold of the AHA/ACC guideline (i.e., SBP> = 130 mmHg or DBP> = 80 mmHg), 3, 015 (58.9%) were identified with hypertension. Multivariate logistic regression using age, sex, smoking, alcohol use, diabetes, and history of MI or stroke as covariates showed a significant association between hypertension and age (<40: OR = 1.13, 95 CI:1.11–1.15, > = 40: OR = 1.05 95% CI:1.04–1.06), male (OR = 1.57, 95% CI:1.33–1.89), alcohol use (OR = 1.59, 95% CI:1.30–1.93), and diabetes (OR = 2.63, 95% CI:1.93–3.58). Conclusions: MMM 2021 in Nepal found more than half of the adults in communities were undiagnosed and untreated. Community-based campaigns such as MMM are meaningful for countries to collect hypertension cascade data in hard-to-reach areas and identify those at high-risk.